An empirical study on students’ ability to comprehend design patterns - Chatzigeorgiou, Alexander; Tsantalis, Nikolaos; Deligiannis, Ignatios (Computers and education, 2008)
Design patterns have become a widely acknowledged software engineering practice and therefore have been incorporated in the curricula of most computer science departments. This paper presents an observational study on students’ ability to understand and apply design patterns. Within the context of a postgraduate software engineering course, students had to deliver two versions of a software system; one without and one with design patterns. The former served as a poorly designed system suffering from architectural problems, while the latter served as an improved system where design problems had been solved by appropriate patterns. The experiment allowed the quantitative evaluation of students’ preference to patterns. Moreover, it was possible to assess students’ ability in relating design problems with patterns and interpreting the impact of patterns on software metrics. The overall goal was to empirically identify ways in which a course on design patterns could be improved.